∫ 0 π / 2 ln ( cos ( x ) ) ln ( sin ( x ) ) sin ( 2 x ) d x .
Evaluate the above integral. If your answer comes in form of b a − d π c , where g cd ( a , b ) = 1 . Then find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can write the integral as :-
2 ∫ 0 2 π ln ( cos ( x ) ) ln ( sin ( x ) ) sin ( x ) cos ( x ) d x
Substituting sin ( x ) = t we have:-
2 ∫ 0 1 ln ( 1 − t 2 ) t ln ( t ) d t = ∫ 0 1 ln ( 1 − t 2 ) t ln ( t ) d t
Now we know that − ln ( 1 − x ) = r = 1 ∑ ∞ r x r for − 1 ≤ x < 1
Hence − ln ( 1 − x 2 ) = r = 1 ∑ ∞ r x 2 r for − 1 ≤ x < 1
Hence we have :-
− r = 1 ∑ ∞ ∫ 0 1 r t 2 r + 1 ln ( t ) d t
Substituting t = e − z we have :-
r = 1 ∑ ∞ ∫ 0 ∞ r e − z ( 2 r + 2 ) z d z
Now substitute ( 2 r + 2 ) z = y
r = 1 ∑ ∞ ∫ 0 ∞ r ( 2 r + 2 ) 2 e − y y d y = 4 1 r = 1 ∑ ∞ r ( r + 1 ) 2 1
= 4 1 r = 1 ∑ ∞ ( r + 1 ) 1 ( r 1 − r + 1 1 ) = 4 1 r = 1 ∑ ∞ ( r 1 − r + 1 1 ) − 4 1 r = 1 ∑ ∞ ( r + 1 ) 2 1
Note here that the splitting of the sums are possible due to convergence of both the sums by Limit Comparison Test.
= 4 1 − 4 1 ( ζ ( 2 ) − 1 ) = 4 1 + 4 1 − 2 4 π 2 = 2 1 − 2 4 π 2
Problem Loading...
Note Loading...
Set Loading...
Since β ( a , b ) = 2 ∫ 0 π / 2 ( sin x ) 2 a − 1 ( cos x ) 2 b − 1 d x , we have by differentiating twice that
∫ 0 π / 2 ln ( sin x ) ln ( cos x ) sin ( 2 x ) d x = 4 1 ∂ a ∂ b ∂ 2 ( β ( a , b ) ) ∣ a = b = 1
It can be proved that ∂ a ∂ b ∂ 2 ( β ( a , b ) ) ∣ a = b = 1 = ( ψ ( 1 ) − ψ ( 2 ) ) 2 − ψ ( 1 ) ( 2 ) = 2 − 6 π 2
Thus ∫ 0 π / 2 ln ( sin x ) ln ( cos x ) sin ( 2 x ) d x = 2 1 − 2 4 π 2 making the answer 2 9
Note: ∂ a ∂ b ∂ 2 ( β ( a , b ) ) = β ( a , b ) [ ( ψ ( a ) − ψ ( a + b ) ) ( ψ ( b ) − ψ ( a + b ) ) − ψ ( 1 ) ( a + b ) ]